THE EFFECT OF SERVICE QUALITY ON PATIENT SATISFACTION AT UPTD PUBLIC HEALTH CENTRE GUNUNGSITOLI - Melini Valencia Howu-Howu Hulu; Fatolosa Hulu; Envilwan Berkat Harefa (Jurnal Ekonomi, 2022)
This study aims to analyze the effect of service quality on patient satisfaction. As a health service, the ability of Public health centres to meet patient needs can be measured by the level of patient satisfaction. Patient satisfaction is related to health services. A health agency, one of which is a Public health centre, in making efforts to improve the quality of health services, it is necessary to measure patient satisfaction. The research method used is a quantitative survey to determine the effect of service quality variables on patient satisfaction variables. The population in this study were UPTD patients at the Gunungsitoli District Health Center. A regression test using SPSS 22 is used for hypothesis testing. The results showed a significant effect between service quality and patient satisfaction, evidenced by the positive service quality regression coefficient of 0.285. The variables of service quality and patient satisfaction have a significant positive relationship as evidenced by the results of correlation analysis obtained by R of 0.630, which indicates that there is a strong relationship between service quality and patient satisfaction, namely rcount = 0.630 and rtable = 0.279, where obtained 0.630 > 0.279.